Idiopathic congenital lymphedema involving the upper limb: A case report - Varughese, Pearl Mary (Indian Journal of Child Health, 2018)
Congenital lymphedema is the rarest form of primary lymphedema. The best line of investigation is lymphoscintigram. The management of primary lymphedema is usually conservative with bed rest and skin care. The prognosis is usually good if there are no other complications. We report a case of 10-year-old boy presented with a complaint of swelling in left upper limb and scrotal edema soon after birth. Investigations were performed and it turned out to be a case of congenital lymphedema involving the upper limb. Although there are many cases of lower limb involvement, upper limb lymphedema has not been documented often, so we are presenting this case.